Sexual harassment in the hospitality industry --- A study on a Chinese state-owned hotel - ZHANG, LULU (2006)
Based on literature reviews, methodologies, and findings, this paper presents an empirical study of sexual harassment in the hospitality industry. Zhongjing Grand Hotel is used as a case study of sexual harassment in the context of China. The similarities and differences from literatures and research findings are indicated. The research proposes two main arguments: (1) the definitions of sexual harassment need to be improved and specific. (2) sexual harassment can happen every places and every countries, however, sexual harassment in the workplace is undoubtedly addressed by researchers or employees. (3) based on the cultural differences, sexual harassment presents differently in the context of China, (4) the harassed people should take measures to avoid sexual harassment.